Phytochemical and antibacterial assessment of essential oils extracted from aerial parts of cordia dichotoma G. Forst - Saddam Hussain Bughio; Saba Bhatti; Shahabuddin Memon; Ayaz Ali Memon; Muhammad Qasim Samejo; Roomia Memon; Mohsin Kazi; Khalid Hussain Thebo (International Journal of Food Properties)
This study involved the exploration of hydro-distilled essential oil (EsO) from the aerial parts of Cordia dichotoma fruits, stems, seeds and leaves via gas chromatography‒mass spectrometry. Approximately 33 volatile components were detected throughout the study. Almost 27 and 23 compounds (comprising 64.83% and 31.55%, respectively, of the total components) were detected in the fruits and stems, whereas 25 compounds (57.12% of the total components) were detected in the seeds, and 25 compounds (52.48% of the total components) were found in the leaves. The main components of the fruit oil were Nonanal (5.77%), Oleic acid (4.30%), β-Damascenone (4.12%), 3, 4-Dehydro-β-ionone (4.06%), Methyl jasmonate (3.32%), Sabinene (3.31%), Phytol (3.22%) and Vitispirane (3.11%). From stem oil, the major components were Nonanal (6.52%), Nonadecane (3.22%) and 2, 3-Octanedione (2.16%). Whereas, the major components of the seed oils were Nonanal (12.14%), Oleic acid (5.13%), Dihydroactindiolide (3.35%), 2-Methoxy-4-vinylphenol (3.18%), Dodecanoic acid (3.16%) and Methyl jasmonate (3.11%). Similarly, the major components of the leaf oils were 2, 4-di-t-Butylphenol (10.25%), 3-Methylnonane (4.73%), 2-Undecanol (4.64%), 3, 4-Dehydro-β-ionone (3.52%) and Nonanal (3.16%). These EsO were used for antibacterial activity against two bacteria i.e. E. coli (G-ve) and the S. aureus (G+ve) by disc diffusion method to determine the MIC (minimum inhibitory concentration) and MBC (maximum bactericidal concentration). However, among the four parts of C. dichotoma, fruit and seed EsO were highly effective against E. coli (MIC and MBC were 125 μg/mL, 1000 μg/mL respectively) compared to S. aureus (MICs of 250 and 500 μg/mL with an MBC of 1000 μg/mL)